Billions. The final season [videorecording (DVD)] - Koppelman, Brian; Levien, David; Sorkin, Andrew Ross (Paramount, 2024)
It takes one to break one in a final season like no other. Bobby Axelrod and Chuck Rhoades have been both adversaries and allies, but when Axe returns with a score to settle, the stakes escalate beyond Wall Street and their game of one-upmanship threatens to topple empires. It'll be a triumph for some, and a tumble for others. This four-disc collection includes every episode and exclusive special features.